PERFORMANCE OF EDUCATION GRADUATES IN THE LICENSURE EXAMINATION FOR TEACHERS (LET) - Antiojo, Ligaya (PEOPLE: International Journal of Social Sciences, 2017)
Passing the Licensure Examination for Teachers (LET) is an indication of quality education offered by Teacher Education Institutions (TEI’s) in the country. In response to the call for academic excellence, this study analyzed the results of the performance of Bachelor of Secondary Education (BSEd) and Bachelor of Elementary Education (BEEd) graduates of Cavite State University Naic in LET from 2013 to 2015 through documentary analysis and descriptive-correlational research. Analysis of the LET Performance revealed that the institutions’ passing percentage in terms of number of passers, on the average, is above the LET National Passing Percentage for both the secondary and elementary education graduates. LET takers recorded the highest average ratings in general education followed by professional courses while the lowest was attained by the BSEd takers in major courses. English major recorded the highest average ratings, followed by Math major, while Biological Science major lagged behind. The LET performance of the first takers exceeds those of the repeaters. Possible interventions were suggested to strengthen instructions and enhance LET Performance. It is likewise recommended to study the predictors of LET Performance in the future researches.